Analisis Hubungan Keberadaan Suaka Perikanan dengan Pendapatan Asli Daerah Kabupaten Ogan Komering Ilir dari Hasil Lelang Lebak Lebung - Apriyanto, F; Irawan, I; Muslim, M (Seminar Nasional Lahan Suboptimal, 2022)
Apriyanto F, Irawan, I, Muslim M. 2022. Analysis of the relationship between existence of  fishery-protected areas and original local government revenue of Ogan Komering Ilir Regency from Lelang Lebak Lebung Revenue. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 443-449.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Fishery protected areas function to preserve fish resources. This area plays an important role in maintaining fish production. This study aimed  to analyze the relationship between the existence of fishery-protected areas and the original local government revenue of Ogan Komering Ilir Regency. The method used is a desk study. The data obtained were analyzed descriptively. The results of the study show that revenue from L3S in sub-districts that have fishery-protected areas is higher than in those that do not. Jejawi District has the most fishery-protected areas, contributing the most to OKI Regency's original local government revenue. To increase L3S revenue, it is recommended to add the number of fishery-protected areas.